Differences in the physical condition of the volleyball players of PBV spirits and PBV mutiara in Sleman regency - Afnan Wijayanto; Prasetyo, Heru; Abdi Pangestu Alam; Risma Oktaviyani; Amru Riyas Rofiyandana; Gibran Ikranegara; Yusuf Wiji Ramadhan; Muhammad Dymas Eka Saputra; Rama Hesa; Muhammad Iqbal Faza; Aiman Anwar (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2025)
This study aims to determine the differences in the physical condition of male and female volleyball athletes between PBV Spirits and PBV Mutiara in Sleman Regency. The physical condition components assessed include coordination, arm power, leg power, agility, speed, flexibility, arm muscle strength, and VO₂Max endurance. The study used a comparative descriptive design with total sampling techniques on 153 athletes. The research instruments included tennis ball throw and catch tests, basketball throw tests, vertical jump tests, Illinois Agility Tests, 40-metre runs, sit and reach tests, pushup tests, and multistage fitness tests. Data analysis was performed using an independent sample t-test. The results showed that among male athletes, PBV Mutiara had better coordination, arm power, flexibility, and VO₂Max, while PBV Spirits had better speed. There were no differences in leg power, agility, and arm muscle strength. In female athletes, PBV Mutiara excelled in coordination and VO₂Max, while PBV Spirits excelled in speed and arm muscle strength. Arm power, leg power, agility, and flexibility did not show significant differences. The conclusion of this study shows that there are differences in certain physical conditions between clubs, which can be used as a basis for evaluating and planning volleyball training programmes.